Method for producing ceramic particle reinforced aluminum matrix composite
By selecting ceramic particles and aluminum alloy powder of appropriate particle size, and combining roller ball milling and staged sintering and hot pressing processes, the forming problem of ceramic particle reinforced aluminum matrix composites was solved, the density of the material and the uniformity of ceramic particle distribution were improved, and high-performance composite materials were prepared.
Patent Information
- Application Number
- CN202311023708.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-15
- Publication Date
- 2025-11-25
- Estimated Expiration
- 2043-08-15
AI Technical Summary
When preparing ceramic particle-reinforced aluminum matrix composites using traditional powder metallurgy methods, it is difficult to press and form them, and through-cracks and sintering pores are prone to occur. Ceramic particles also tend to agglomerate, affecting the material's density.
Ceramic particles with a median diameter of 1µm to 5µm and a particle size concentration factor of 2.0 to 3.0 are mixed with aluminum alloy powder with a median diameter of 3µm to 10µm. After being uniformly mixed by roller ball milling, the mixture is molded at 100℃ to 150℃, and then sintered and hot-pressed in stages. The sintering process is controlled, and finally hot-pressed and shaped at 540℃ to 600℃.
This method enables easy pressing and forming, reduces porosity, improves ceramic particle distribution, and produces ceramic particle-reinforced aluminum matrix composites with a density as high as 99.1%.
Abstract
Description
Technical Field
[0001] This invention relates to the field of powder metallurgy technology, and in particular to a method for preparing ceramic particle-reinforced aluminum matrix composites. Background Technology
[0002] Ceramic particle-reinforced aluminum matrix composites exhibit low density, high specific strength and stiffness, high thermal conductivity, and excellent wear resistance and corrosion resistance, making them promising candidates for lightweight structural components. Powder metallurgy offers advantages such as low cost, stable quality, and continuous precision forming. Using powder metallurgy to prepare ceramic particle-reinforced aluminum matrix composites allows for wide-range control of ceramic particle content, improving particle distribution uniformity and enhancing overall material performance. However, traditional powder raw materials are difficult to press into shape during powder metallurgy preparation. Even when pressed, through-cracks are common, leading to numerous sintering pores, ceramic particle agglomeration, and reduced material density. Summary of the Invention
[0003] Therefore, it is necessary to provide a method for preparing ceramic particle-reinforced aluminum matrix composites that are easy to press and form and have high density.
[0004] A method for preparing a ceramic particle-reinforced aluminum matrix composite material includes the following steps:
[0005] Ceramic particles with a median diameter of 1µm to 5µm and a particle size concentration factor of 2.0 to 3.0 are provided.
[0006] We provide aluminum alloy powder with a median diameter of 3µm to 10µm;
[0007] The ceramic particles and aluminum alloy powder were mixed evenly using a ball milling method to obtain a mixed powder.
[0008] The mixed powder is molded at 100℃~150℃, sintered and hot-pressed to obtain a ceramic particle reinforced aluminum matrix composite material.
[0009] In one embodiment, the ball-to-material ratio in the ball milling method is 1:1 to 2:1, the rotation speed is 60 r / min to 90 r / min, and the mixing time is 1 h to 2 h.
[0010] In one embodiment, the feed volume in the ball milling method is 1 / 3 to 2 / 3 of the mixing container volume.
[0011] In one embodiment, the compression molding pressure is 200MPa to 400MPa, and the holding time is 1 to 2 minutes.
[0012] In one embodiment, the sintering conditions are as follows: first, the temperature is increased to 460°C to 480°C at a rate of 2°C / min to 5°C / min, and held for 30 to 50 minutes; then, the temperature is increased to 560°C to 580°C at a rate of 2°C / min to 5°C / min, and held for 60 to 80 minutes; finally, the temperature is increased to 650°C to 680°C at a rate of 5°C / min to 10°C / min, and held for 150 to 200 minutes.
[0013] In one embodiment, the hot pressing temperature is 540°C to 600°C and the pressure is 300MPa to 500MPa.
[0014] In one embodiment, the ceramic particles and aluminum alloy powder are mixed at a mass ratio of 1:9 to 2:3.
[0015] In one embodiment, the ceramic particles are selected from at least one of carbides, nitrides, oxides, silicides, and borides.
[0016] In one embodiment, the aluminum alloy powder is a B-series aluminum alloy or a B-series aluminum alloy.
[0017] In one embodiment, the aluminum alloy powder is nitrogen-atomized spherical aluminum alloy powder.
[0018] The above-mentioned method for preparing ceramic particle-reinforced aluminum matrix composites involves selecting ceramic particles with a median diameter of 1µm to 5µm and a particle size concentration factor of 2.0 to 3.0, and aluminum alloy powder with a median diameter of 3µm to 10µm. This method ensures the strength of the powder compact while improving the compaction performance of the powder. The powder compact, after being molded at 100℃ to 150℃, has lower porosity, which improves the problem of easy agglomeration of ceramic particles during sintering. Finally, after hot pressing and shaping, a high-density ceramic particle-reinforced aluminum matrix composite is obtained. Detailed Implementation
[0019] To facilitate understanding of the present invention, a more comprehensive description is provided below, along with preferred embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention.
[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0021] A method for preparing a ceramic particle-reinforced aluminum matrix composite material according to one embodiment includes the following steps S110 to S140:
[0022] S110 provides ceramic particles with a median diameter of 1µm to 5µm and a particle size concentration factor of 2.0 to 3.0.
[0023] In this embodiment, the ceramic particles are selected from at least one of carbides (such as TiC, SiC, B4C, etc.), nitrides (such as Si3N4), oxides (such as Al2O3), silicides (such as Ti5Si3), and borides (such as TiB, TiB2, etc.).
[0024] Furthermore, the median diameter of the ceramic particles is 3µm to 4µm, and the particle size distribution factor is 2.3 to 2.5.
[0025] S120 provides aluminum alloy powder with a median diameter of 3µm to 10µm.
[0026] In this embodiment, the aluminum alloy powder is a binary aluminum alloy or a hexagonal aluminum alloy. The binary aluminum alloy is an aluminum alloy with copper as the main alloying element, including Al-Cu-Mg alloys, Al-Cu-Mg-Si alloys, etc.; the hexagonal aluminum alloy is an aluminum alloy with magnesium and silicon as the main alloying elements and Mg2Si phase as the strengthening phase, including Al-Mg-Si alloys, etc.
[0027] Furthermore, the Al-Mg-Si alloy is Al-1Mg-0.7Si-0.25Cu (i.e., this alloy mainly consists of 1% Mg, 0.7% Si, 0.25% Cu, and the balance Al) or Al-0.6Mg-0.9Si (i.e., this alloy mainly consists of 0.6% Mg, 0.9% Si, and the balance Al). The Al-Cu-Mg alloy is Al-4Cu-0.8Mg (i.e., this alloy mainly consists of 4% Cu, 0.8% Mg, and the balance Al). The Al-Cu-Mg-Si alloy is Al-2Cu-0.5Mg-0.7Si-0.5Mn (i.e., this alloy mainly consists of 2% Cu, 0.5% Mg, 0.7% Si, 0.5% Mn, and the balance Al).
[0028] Furthermore, the aluminum alloy powder is nitrogen-atomized spherical aluminum alloy powder.
[0029] Using nitrogen-atomized spherical aluminum alloy powder combined with ceramic particles can increase the powder's fluidity, making it easier to fill the mold cavity during subsequent molding and resulting in a uniform density distribution of the pressed blank.
[0030] By selecting ceramic particles with a particle size concentration coefficient of 2.0 to 3.0 and a median diameter of 1 μm to 5 μm and aluminum alloy powder with a median diameter of 3 μm to 10 μm, the small particles can be uniformly filled into the pores of the large particles. In the subsequent molding process, the density and strength of the compact can be effectively increased, the elastic aftereffect can be reduced, and a qualified compact with high density and uniform ceramic particle distribution can be obtained.
[0031] S130. The above ceramic particles and aluminum alloy powder are mixed evenly using a roller ball milling method to obtain a mixed powder.
[0032] In this embodiment, the ball-to-material ratio in the drum ball mill is 1:1 to 2:1, the rotation speed is 60 r / min to 90 r / min, and the mixing time is 1 h to 2 h. The feeding volume is 1 / 3 to 2 / 3 of the mixing container volume.
[0033] It is understandable that the aforementioned "feeding" refers to the ceramic particles and aluminum alloy powder being added into the mixing container.
[0034] Furthermore, ceramic particles and aluminum alloy powder are mixed at a mass ratio of 1:9 to 2:3. Even further, ceramic particles and aluminum alloy powder are mixed at a mass ratio of 1:4.
[0035] By limiting the ball-to-material ratio, rotation speed, and feed volume in the drum ball milling method, it can be ensured that ceramic particles and aluminum alloy powder can be quickly and evenly mixed without work hardening.
[0036] S140. After molding the above mixed powder at 100℃~150℃, sinter and hot press to obtain ceramic particle reinforced aluminum matrix composite material.
[0037] In this embodiment, the compression molding pressure is 200MPa to 400MPa, and the holding time is 1 to 2 minutes.
[0038] By molding at 100℃~150℃, the mixed powder can achieve a higher density at a lower temperature, reducing shrinkage and deformation during subsequent sintering and improving the efficiency and quality of subsequent sintering.
[0039] In this embodiment, the sintering conditions are as follows: first, the temperature is increased to 460℃ to 480℃ at a rate of 2℃ / min to 5℃ / min, and held for 30 to 50 minutes; then, the temperature is increased to 560℃ to 580℃ at a rate of 2℃ / min to 5℃ / min, and held for 60 to 80 minutes; finally, the temperature is increased to 650℃ to 680℃ at a rate of 5℃ / min to 10℃ / min, and held for 150 to 200 minutes.
[0040] The aforementioned staged sintering can effectively control the reaction rate of ceramic particles and aluminum alloy powder, avoid generating excessive reaction products and pores, and also facilitate the solid-phase sintering and liquid-phase sintering of aluminum alloy powder, thereby improving the mechanical properties of the composite material.
[0041] In this embodiment, the temperature for hot pressing is 540℃~600℃, and the pressure is 300MPa~500MPa.
[0042] The above method can prepare ceramic particle reinforced aluminum matrix composites with uniform ceramic particle distribution and a density of over 99.1%.
[0043] The following are specific examples.
[0044] Example 1
[0045] A drum ball mill was used to mix ceramic particles with a median diameter of 3.92 μm and a particle size concentration factor of 2.39 and aluminum alloy powder with a median diameter of 6.48 μm at a mass ratio of 1:4 to obtain a mixed powder. The ball-to-material ratio in the drum ball mill was 1:1, the rotation speed was 80 r / min, the mixing time was 2 h, and the feeding volume was 1 / 3 of the volume of the mixing container.
[0046] The above-mentioned mixed powder is molded at 100℃ and 200MPa for 1 to 2 minutes to obtain a powder compact.
[0047] The powder compact was sintered under the following conditions: first, the temperature was increased to 460°C at a rate of 5°C / min and held for 30 minutes; then, the temperature was increased to 560°C at a rate of 5°C / min and held for 60 minutes; finally, the temperature was increased to 660°C at a rate of 10°C / min and held for 180 minutes to obtain the sintered compact.
[0048] The above sintered blank was hot-pressed at 560℃ and 400MPa to obtain a ceramic particle reinforced aluminum matrix composite material.
[0049] The density of the composite material prepared in Example 1 was found to be 99.5%.
[0050] Comparative Example 1
[0051] Comparative Example 1 is basically the same as Example 1, except that the median diameter of the ceramic particles used in Comparative Example 1 is 3.5 μm and the particle size concentration factor is 1.2.
[0052] The density of the composite material prepared in Comparative Example 1 was found to be 98.5%.
[0053] Comparative Example 2
[0054] Comparative Example 2 is basically the same as Example 1, except that the median diameter of the aluminum alloy powder used in Comparative Example 2 is 11.29 μm.
[0055] The density of the composite material prepared in Comparative Example 2 was tested and found to be 97.8%.
[0056] Comparative Example 3
[0057] Comparative Example 3 is basically the same as Example 1, except that the median diameter of the aluminum alloy powder used in Comparative Example 3 is 19.00 μm.
[0058] The density of the composite material prepared in Comparative Example 3 was found to be 96.1%.
[0059] Comparative Example 4
[0060] Comparative Example 4 was basically the same as Example 1, except that compression molding was carried out at room temperature. As a result, the compact developed through cracks and could not be molded.
[0061] Comparative Example 5
[0062] Comparative Example 5 was basically the same as Example 1, except that the molding temperature was 50°C and the pressure was 200 MPa. The results showed that cracks were generated in the compact, the density of the prepared composite material was 98.8%, and the cracks did not heal in the end.
[0063] Comparative Example 6
[0064] Comparative Example 6 is basically the same as Example 1, except that the sintering conditions are: directly heating to 660°C at a rate of 5°C / min and holding for 180 minutes.
[0065] The density of the composite material prepared in Comparative Example 6 was found to be 98.1%, indicating that the lack of segmented heat preservation and the oxide film on the surface of the aluminum alloy powder hindered the sintering process.
[0066] Comparative Example 7
[0067] Comparative Example 7 is basically the same as Example 1, except that Comparative Example 7 uses anhydrous ethanol as the medium for ball milling and mixing for 2 hours.
[0068] Testing revealed that the density of the composite material prepared in Comparative Example 7 was 98.2%, and that ceramic particles agglomerated, indicating that the raw materials were not mixed evenly.
[0069] Example 2
[0070] A ball milling method was used to mix ceramic particles with a median diameter of 1 μm and a particle size concentration factor of 2.0 and aluminum alloy powder with a median diameter of 3 μm at a mass ratio of 1:9 to obtain a mixed powder. The ball-to-material ratio in the ball milling method was 2:1, the rotation speed was 60 r / min, the mixing time was 1 h, and the feeding volume was 1 / 3 of the volume of the mixing container.
[0071] The above-mentioned mixed powder is molded at 150℃ and 400MPa for 1 to 2 minutes to obtain a powder compact.
[0072] The powder compact was sintered under the following conditions: first, the temperature was increased to 480°C at a rate of 2°C / min and held for 50 minutes; then, the temperature was increased to 580°C at a rate of 2°C / min and held for 80 minutes; finally, the temperature was increased to 680°C at a rate of 5°C / min and held for 200 minutes to obtain the sintered compact.
[0073] The above sintered blank was hot-pressed at 600℃ and 300MPa to obtain a ceramic particle reinforced aluminum matrix composite material.
[0074] The density of the composite material prepared in Example 2 was found to be 99.1%.
[0075] Example 3
[0076] The ceramic particles with a median diameter of 5 μm and a particle size concentration factor of 3.0 and the aluminum alloy powder with a median diameter of 10 μm were mixed evenly at a mass ratio of 2:3 using a drum ball milling method to obtain a mixed powder. The ball-to-material ratio in the drum ball milling method was 1:1, the rotation speed was 90 r / min, the mixing time was 2 h, and the feeding volume was 2 / 3 of the volume of the mixing container.
[0077] The above-mentioned mixed powder is molded at 120℃ and 300MPa for 1 to 2 minutes to obtain a powder compact.
[0078] The powder compact was sintered under the following conditions: first, the temperature was increased to 480°C at a rate of 4°C / min and held for 40 minutes; then, the temperature was increased to 580°C at a rate of 4°C / min and held for 70 minutes; finally, the temperature was increased to 650°C at a rate of 8°C / min and held for 150 minutes to obtain the sintered compact.
[0079] The above sintered blank was hot-pressed at 540℃ and 500MPa to obtain a ceramic particle reinforced aluminum matrix composite material.
[0080] The density of the composite material prepared in Example 3 was found to be 99.3%.
[0081] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. A method for preparing a ceramic particle-reinforced aluminum matrix composite material, characterized in that, Includes the following steps: Ceramic particles with a median diameter of 1 μm to 5 μm and a particle size concentration factor of 2.0 to 3.0 are provided. We provide aluminum alloy powder with a median diameter of 3μm to 10μm; The ceramic particles and aluminum alloy powder were mixed evenly using a ball milling method to obtain a mixed powder. The mixed powder is molded at 100℃~150℃, then sintered and hot-pressed to obtain a ceramic particle reinforced aluminum matrix composite material. In the described drum ball milling method, the ball-to-material ratio is 1:1 to 2:1, the rotation speed is 60 r / min to 90 r / min, and the mixing time is 1 h to 2 h. In the aforementioned ball milling method, the feed volume is 1 / 3 to 2 / 3 of the mixing container volume.
2. The method for preparing ceramic particle-reinforced aluminum matrix composite material according to claim 1, characterized in that, The compression molding pressure is 200MPa to 400MPa, and the holding time is 1 to 2 minutes.
3. The method for preparing ceramic particle-reinforced aluminum matrix composite material according to claim 1, characterized in that, The sintering conditions are as follows: first, the temperature is increased to 460℃~480℃ at a rate of 2℃ / min~5℃ / min, and held for 30~50 minutes; then, the temperature is increased to 560℃~580℃ at a rate of 2℃ / min~5℃ / min, and held for 60~80 minutes; finally, the temperature is increased to 650℃~680℃ at a rate of 5℃ / min~10℃ / min, and held for 150~200 minutes.
4. The method for preparing ceramic particle-reinforced aluminum matrix composite material according to claim 1, characterized in that, The hot pressing temperature is 540℃~600℃, and the pressure is 300MPa~500MPa.
5. The method for preparing ceramic particle-reinforced aluminum matrix composite material according to claim 1, characterized in that, The ceramic particles and aluminum alloy powder are mixed at a mass ratio of 1:9 to 2:
3.
6. The method for preparing ceramic particle-reinforced aluminum matrix composite material according to any one of claims 1 to 5, characterized in that, The ceramic particles are selected from at least one of carbides, nitrides, oxides, silicides, and borides.
7. The method for preparing ceramic particle-reinforced aluminum matrix composite material according to any one of claims 1 to 5, characterized in that, The aluminum alloy powder is a B2 series aluminum alloy or a 6 series aluminum alloy.
8. The method for preparing ceramic particle-reinforced aluminum matrix composite material according to any one of claims 1 to 5, characterized in that, The aluminum alloy powder is nitrogen-atomized aluminum alloy powder.
Citation Information
Patent Citations
Silicon carbide particle reinforced aluminum-based composite material as well as preparation method and application thereof
CN114086037A
Shape memory ceramic reinforced aluminum-based composite material and preparation method capable of regulating and controlling austenite content
CN115570132A